X‐ray structure of host‐guest nanosized organotin supramolecular coordination polymer based on cobalt cyanide and quinoxaline as an efficient catalyst for treatment of waste water. (21st January 2020) - Etaiw, Safaa Eldin H.; Abd El‐Aziz, Dina M.; Shalaby, Elsayed M.; Elzeny, Islam
Abstract : New host‐guest supramolecular coordination polymer catalyst 3 ∞ [Co(μ 2 CN)5 (CN)(μ 2 ‐Me3 Sn)2 (Me3 Sn)(H2 O)(qox)], SCP1 (qox = quinoxaline) has been synthesized and characterized by single crystal X‐ray diffraction, FT‐IR, U V /Visible and fluorescence spectra, thermal and elemental analyses. The tin atoms act as bridges connecting the Co (CN)6 building blocks. The structure of SCP1 exhibits an unusual self‐coordinated host‐guest 3D network with qox as guest molecule. Also, the nanosized1 \ was prepared under ultrasonic irradiation while the morphological features of both were examined by TEM and SEM. SCP1 and nanosized1 \ are used as heterogeneous catalysts for removal of toxic dyes under UV and ultrasonic irradiation. The results show high effectively decolorized of indigo carmine dye (IC) without generation of any hazardous wastes or byproducts. The reaction is first order with respect to IC, while the factors affecting the rate constant of the degradation reaction are investigated. Mineralization of IC was investigated by IR and UV spectra. The trapping experiments were carried out to determine the role of active species used for degradation of the dye. The activation parameters of the reaction have been estimated and a possible mechanism of degradation was proposed and discussed in detail. Abstract : New host‐guest supramolecular coordination polymer catalyst 3∞[Co(µ2CN)5(CN)(μ2‐Me3Sn)2(Me3Sn)(H2O)(qox)], SCP1 (qox = quinoxaline) hasbeen synthesized and characterized. The nanosized1\ are prepared under ultrasonicirradiation and their morphological features were examined. SCP1 and nanosized1\ are used as heterogeneouscatalysts for removal of toxic dyes under UV and ultrasonic irradiation.